Fast Parallels? Contesting Mobile Policy Technologies. (30th October 2017) - Weller, Sally
Abstract: This article extends recent examinations of incomplete or disrupted policy mobility by examining the politically volatile case of policies to manage the regional impacts of decarbonization in Australia. The article's extended case study shows how political interests differently incorporated figments of circulating policy into longstanding debates and how more‐than‐local political networks defeated an antipolitical, technocratic exercise in 'new regional' governance. 'Follow the policy' methods could not have revealed the complexities of this case. The article concludes that mobilities approaches need to be more attentive to institutional arrangements, to the contested politics of policy formation and to the ambiguities of perceived policy likenesses. This case highlights the importance of considering how antipolitical institutional architectures facilitating policy mobility relate to established political power networks.